Manufacturing of carbon black from spent tyre pyrolysis oil – A literature review. (10th January 2021) - Okoye, Chiemeka Onyeka; Jones, Isabelle; Zhu, Mingming; Zhang, Zhezi; Zhang, Dongke
Abstract: Carbon black (CB) is a carbon material produced by either thermal decomposition or incomplete combustion of hydrocarbons under controlled conditions. With industrial applications as an elastomer-reinforcing agent, a conductive filler, a coating agent, a dyeing agent and adsorbent for heavy metal removal, CB is listed as one of the top 50 industrial chemicals globally. The current feedstocks utilised in CB production are fossil fuel-based resources hence susceptible to volatile oil prices in addition to the associated high CO2 emission. There has been a growing interest in using feedstocks from renewable sources and recycled wastes to produce CB. Guided by the principles of cleaner production, this paper reviews the current state of CB production using renewable and recycled waste resources with a particular feedstock of interest being spent tyre pyrolysis oil. The utilisation of spent tyre pyrolysis oil as a feedstock offers a cleaner production route to CB manufacturing with improved environmental performance and reduced costs. The formation mechanisms and key governing factors for suitable CB feedstock selection are reviewed. Various resources for CB production are summarised and discussed. The chemical compositions and physical properties of spent tyre pyrolysis oil from various processes are analysed and compared with other feedstocks, providing a basis for evaluating the possibility of using spent tyre pyrolysis oil for CB production. Graphical abstract: Image 1 Highlights: Carbon black production from renewable and wastes resources systematically reviewed. Aromaticity, C/H and sulphur contents are key factors in feedstock selection. Spent tyre pyrolysis oil is a feasible feedstock for premium carbon black production. Yield and structural properties of CB from pyrolysis oil need to be examined. Conversion of spent tyre oil to CB follows the cleaner production principles.